Age and anti‐Müllerian hormone levels predict the success of in vitro maturation of cat oocytes. (15th November 2016) - Snoeck, F; Sarrazin, S; Wydooghe, E; Van Soom, A
Contents: Up to date, in vitro maturation (IVM) rates of oocytes are highly variable between individual cats. This study was carried out to investigate the predictive value of age and anti‐Müllerian hormone (AMH) concentration in relation to capacity for IVM of cat oocytes. Ovaries were collected from 33 cats, which were divided into three age groups: (i) 0–3 months (pre‐pubertal); (ii) 3–12 months (peripubertal); and (iii) older than 12 months (pubertal). The cumulus–oocyte complexes (COCs) were matured and subsequently stained to check nuclear maturation status, and blood was taken for AMH analysis. Increasing age was significantly associated with decreasing AMH levels, and mean AMH levels differed significantly between all age categories: group 1: mean AMH 18.71 μg/L; group 2: mean AMH 9.27 μg/L; and group 3: mean AMH 4.13 μg/L. Moreover, the probability of maturation was more likely in groups 2 and 3 compared to group 1. Between categories 2 and 3, no significant difference in maturation probability was found ( p  = .31). Finally, the probability of oocyte maturation decreased significantly with increasing AMH levels. In age group 2, oocytes with a higher AMH level were less likely to mature. In age groups 1 and 3, no significant association between the AMH level and the proportion of maturated COC was found. We can conclude that if a higher probability of nuclear maturation is required, it is preferable to use cats with lower AMH levels and older than 3 months of age to improve cat IVM.